(untitled) (European Journal of Language and Literature, 2018)
Although they elaborate it differently, both Levinas and Deleuze appeal to the notion of rhythm as decisive for understanding art. Drawing on their analyses I discuss the work of several artists featured in a current exhibit showing at the Tate Britain, All Too Human: Bacon, Freud and a Century of Painting Life. In addition to Francis Bacon and Lucian Freud, I discuss the work of Paula Rego and Lynette Lydiam-Boakye. Vlad Ionescu suggests that a productive approach to writing about art after Deleuze and Guattari would be to inquire into ‘how constellations of sensation modify our perceptions of the world’ (2017, p. 22). I take up Ionescu’s suggestion, but also recontexutalize it in order to offer a politicized account of how the exhibit is framed. At the same time I draw on feminist and race theory to discuss the work of Rego and Lydiam-Boakye, thus also recontextualizing Levinas’s and Deleuze’s analyses of art. The questions this paper addresses include: What makes these paintings work, and how do they function? How do their aspects and rubrics operate? What creates their rhythms? How do they operate as an assemblage?